Refleksi Perilaku Asosial Akibat Pengaruh Media Sosial Dalam Karya Seni Rupa Posmodern (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
The development of technology specifically social media in modern era, has brought peoples to the global network and excessive connectivity. In line with that, humans are immersed in cyberspace which acts artificially. Social activities in the real world are replaced by the forms of cyberspace activities, thus affecting patterns of human social behavior. One of them is asocial behavior that emerged because peoples are accustomed to living in cyberspace. Because social interaction that exists in the real world does not occur, many people being ignorant of their social environment. Today many people are more comfortable interacting in cyberspace while they are gathering with others, even though the social interactions should occur there, in the real world. This phenomenon is then reflected in postmodern artwork using postmodernism studies such as the Baudrillard’s Hyperreality Theory and Lyotard’s Postmodern Theory. This study used artistic research methods to overshadow the entire research process starting from the conceptual aspect, the visual aspect, to the process of producing in the operational aspect. Humans confront various problems and dynamics in life that eventually become a life experience. The experience can be reflected through the media of art so that it can be visually spoken and become an education for others. Like the work in this thesis which is a self-reflection of asocial experiences due to the influence of social media that displayed through visuals, techniques, and the process of creating postmodern art.